Iminyl-radicals by electrochemical decarboxylation of α-imino-oxy acids: construction of indole-fused polycyclics. Issue 79 (16th September 2021) - Wan, Jin-Lin; Cui, Jian-Feng; Zhong, Wei-Qiang; Huang, Jing-Mei
Abstract : An electrochemical decarboxylation/N–O bond cleavage of α-imino-oxy acids was achieved to build up N-heterocycles via iminyl radicals. Abstract : Iminyl radicals are reactive intermediates that can be used for the construction of various valuable heterocycles. Herein, the electrochemical decarboxylation of α-imino-oxy acids for the generation of iminyl radicals has been accomplished under exogenous-oxidant- and metal-free conditions through the use of n Bu4 NBr as a mediator. The resulting iminyl radicals undergo intramolecular cyclization smoothly with the adjacent (hetero)arenes to afford a series of indole-fused polycyclic compounds.